Effects of Dietary Standardized Ileal Digestible Lysine on Growth Performance, Carcass Characteristics, and Economics of Pigs from 230 to 285 lb - Hilario M. Cordoba; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 1,570 finishing pigs (337 × 1050, PIC; initially 228.4 ± 1.87 lb) were used in a 28-d trial to determine the effects of feeding increasing standardized ileal digestible (SID) Lys to pigs between 230 to 285 lb on growth performance, carcass characteristics, and economics. Prior to the beginning of the study, the three heaviest pigs per pen were removed and marketed, with all remaining pigs marketed 28-d later at the end of the study. Pigs were housed in mixed-sex pens, with 20 pigs per pen and 20 pens per treatment. The experiment was a randomized complete block design with four dietary treatments: 0.61, 0.68, 0.75, and 0.82% SID Lys. Diets were corn-soybean meal-based and fed in meal form. Dietary treatments were similar in NE and increasing SID Lys was achieved by increasing soybean meal and feed-grade amino acids. For the first 14 d from 230 to approximately 260 lb, as SID Lys increased, there was a tendency for increased (linear, P = 0.074) ADG, an improvement (linear, P < 0.05) in F/G, and increase (linear, P < 0.001) in SID Lys intake per kg of gain. For the second 14 d from 260 to 285 lb, SID Lys intake per kg of gain increased (linear, P < 0.001) as SID Lys increased; however, there was no evidence for difference (P > 0.10) for any growth performance traits. Overall, there was an improvement (linear, P < 0.05) in F/G and increase (linear, P < 0.001) in SID Lys intake per kg of gain as SID Lys increased. Increasing SID Lys also increased (linear, P < 0.05) percentage lean and decreased (linear, P < 0.05) backfat depth with no evidence for differences (P > 0.10) in other carcass criteria. For economics, feed cost and feed cost per lb of gain increased (linear, P < 0.05) as SID Lys increased in both low- and high-price scenarios. Income over feed cost decreased (linear, P < 0.05) as dietary SID Lys increased in a low-price scenario, but there was no difference (P > 0.10) between treatments in a high-price scenario. In conclusion, increasing dietary SID Lys in feed offered to pigs remaining in the pen after topping for the last 28-d of the finisher period linearly improved F/G and increased SID Lys intake per kg of gain without significantly influencing other growth performance traits. Feed cost per pound of gain was linearly increased for both low and high-price scenarios with a detriment for IOFC with increasing SID Lys in the low-price scenario.
Keywords: carcass characteristics; finishing pig; growth performance; lysine